Optimization of Liquid Smoke from Shorea pachyphylla using Response Surface Methodology and its Characterization - Hasan Ashari Oramahi; Kustiati; Elvi Rusmiyanto Pancaning Wardoyo (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
The present study aims to optimize the processing variables producing liquid smoke from mabang wood (Shorea pachyphylla) by using Response Surface Methodology (RSM). In this investigation, a design of experiment with different combinations of pyrolysis temperature and pyrolysis time on the liquid smoke yield from mabang wood was applied. The response of the optimal yield, temperature, and time of pyrolysis was predicted using a mathematical model. The optimal operating conditions for the process of yielding 31.31% liquid smoke were identified at the pyrolysis temperature of 440◦C and pyrolysis time of 124 minutes. The effect of pyrolysis temperature was more significant than the pyrolysis time (p<0.05). The liquid smoke samples were evaluated by a GC-MS. The main chemical compound of the liquid smoke were 1,2-ethanediol (19.26%), fluoromethane (6.69%), formic acid (4.96%), 2-propanone (4.17%), acetic acid (18.64%), acetol (4.80%), furfural (9.94%), 2,4-hexadecanoic acid (3.45%), and guaiacol (2.93%).